PROFILE AND VALIDITY OF ELECTRONICS STUDENTS WORKSHEETS BASED ON PROJECT BASED LEARNING ON PLANT GROWTH AND DEVELOPMENT MATERIALS FOR GRADE 12 HIGH SCHOOL - Berliana Melanita; Novita K. Indah (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
The learning process that involves active students is one of them by making innovations in the field of information technology which is currently growing rapidly. This innovation is teaching material. Currently, one of the supports for the learning process and liason between teachers and students is the existence of teaching materials. This study aimed to produce an electronic student work sheet based on PjBL material for growth and development in plants that is theoretically feasible in terms of presentation, content and language aspect through validation by experts. This research uses a 4-D development model (Define, Design, develop and Disseminate) without disseminate. Student worksheet design is carried out at the design stage and the validation is carried out at the develop stage. The data analysis technique uses descriptive qualitative and quantitative. Student worksheet on growth and development materials has been successfully develop with integrated Project Based Learning syntax. The results of the validation are 94% (very valid), in the content aspect 97.5% (very valid), and the language aspect 100% (very valid). This electronic student worksheets have several features that support learning, such as let's review together, finally I Know and the implementation of practicum projects. The results of this study indicate that the PjBL-based e-LKPD is stated to be theoretically feasible in the very valid category and can be tested on a limited basis to determine empirical validity. Keywords: validity, electronic-student work sheet, Project Based Learning